A companion to second-century Christian "heretics" - Luomanen, Petri, 1961-; Marjanen, Antti. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2008, ISBN: 9789004222717., 2008)
The book illuminates "the other side" of early Christianity by examining thinkers and movements that were embraced by many second-century religious seekers as legitimate forms of Christianity, but which are now largely forgotten, or are known only from the characteristics attributed to them in the writings of their main adversaries. The collection deals with the following teachers and movements: Basilides, Sethianism, Valentinus' school, Marcion, Tatian, Bardaisan, Montanists, Cerinthus, Ebionites, Nazarenes, Jewish-Christianity of the Pseudo-Clementines , and Elchasites. Where appropriate, the authors have included an overview of the life and significant publications of the "heretics," along with a description of their theologies and movements. Therefore, this volume can serve as a handbook of the second-century "heretics" and their "heresies." Since all the chapters have been written by specialists who wrestle daily with their research themes, the contributions also offer new perspectives and insights stimulating further discussion on this fascinating-but often neglected-side of early Christianity.